Malaysian hybrid ghazals - Joseph Marshall, Elizabeth Marshall (2022)
The English ghazals originated from Urdu ghazals, which had evolved from Arabia. Melancholia is a central component in such ghazals. Reading English ghazals brought the realisation that this form is suited to themes of heartbreak and unrequited love, one that is also central to my writing. Agha Shahid Ali edited Ravishing DisUnities: Real Ghazals in English (2000) to take back the form and offered a framework. Consequently, I crafted Malaysian hybrid ghazals based on his framework.